Budaya Organisasi Salah Satu Faktor Penentu Kinerja Karyawan - Marlina Deliana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Organizational culture is one of the factors that differentiate the performance results of a company. Organizational culture is proposed to employees as the way a job is done. National and social culture of a country influences organizational culture, based on the Hofstede’s and Trompeneaar’s model, there are dimensions of community culture that influence and shape the values and norms of a founder, employees, and customers of a company. Performance is the result of an employee's ability coupled with effort and support. The ability of an influential person is influenced by talent and interest, while effort is influenced by motivation, incentives and work patterns. The importance of organizational culture on employee performance has two research views. Some researchers consider that organizational culture has no significant effect on performance, while some studies prove that organizational culture has a positive and significant effect on employee performance. Organizational culture that is found in many Indonesians organizational culture is a hierarchical culture, which focuses on control and stability associated with the bureaucratic system. So that this becomes one of the factors, where organizational culture is not a determining factor for improving performance.